Effect of Internet Self-Efficacy on the Adherence of Middle Adulthood M-health Users with Online Trust Behavior as a Mediator Variable - Nawangsih, Endah; Tambunan, Siti Marliah; Putri, Dian Kemala (Universitas Islam Bandung, 2023)
Adherence to treatment regimens is a significant challenge faced by patients with chronic illnesses and healthy individuals, including through m-Health—a new model of remote health delivery via mobile phones. Middle-aged adults often need more internet skills, especially concerning internet self-efficacy and online trust behavior in health services. This study aims to elucidate the relationship between internet self-efficacy and adherence to medical advice among middle-aged m-Health users, mediated by online trust behavior. A cross-sectional study was conducted from 4 July to 4 September 2022, involving 214 respondents selected through convenient sampling from various cities and regencies in Indonesia. Data were collected using online forms distributed to the participants. The statistical analysis employed a structural equation model (SEM) with the LISREL version 8.7. The results showed a chi-square value of 438.61, df=187, p=0.00000, RMSEA=0.079, NFI=0.93, NNFI=0.95, CFI=0.95, and IFI=0.95. These findings indicate that online trust behavior successfully mediates the relationship between internet self-efficacy and adherence. However, internet self-efficacy does not directly affect adherence. This means that adherence will increase when trust in health services.